2015
DOI: 10.1530/eje-15-0381
|View full text |Cite
|
Sign up to set email alerts
|

BclI glucocorticoid receptor polymorphism in relation to cardiovascular variables: the Hoorn and CODAM studies

Abstract: Objective: Excess glucocorticoids are known to cause hypertension and cardiovascular disease (CVD). The BclI glucocorticoid receptor (GR) polymorphism increases glucocorticoid sensitivity and is associated with adverse metabolic effects. Previous studies investigating cardiovascular implications have shown inconsistent results. Therefore, the aim of the present study was to investigate the association of the BclI polymorphism with blood pressure, atherosclerosis, low-grade inflammation, endothelial dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…The Bcl I polymorphism (rs41423247), located in Intron 2, influences GR expression and modulates the GR transcriptional activity of genes responsible for glucose and insulin homeostasis 70 . Homozygous carriers of the Bcl I polymorphism have, compared with noncarriers, more total body fat and insulin resistance, as well as higher blood pressure 71–73 . Carriers of both the Bcl I and N363S polymorphisms had higher blood pressure and higher LDL cholesterol compared with carriers of the N363S polymorphism alone 64 …”
Section: Genetic Mutations and Polymorphisms In Association With Gc Sensitivitymentioning
confidence: 99%
“…The Bcl I polymorphism (rs41423247), located in Intron 2, influences GR expression and modulates the GR transcriptional activity of genes responsible for glucose and insulin homeostasis 70 . Homozygous carriers of the Bcl I polymorphism have, compared with noncarriers, more total body fat and insulin resistance, as well as higher blood pressure 71–73 . Carriers of both the Bcl I and N363S polymorphisms had higher blood pressure and higher LDL cholesterol compared with carriers of the N363S polymorphism alone 64 …”
Section: Genetic Mutations and Polymorphisms In Association With Gc Sensitivitymentioning
confidence: 99%
“…In addition to the N363S polymorphism, the BclI polymorphism of the NR3C1 gene has also been associated with increased glucocorticoid sensitivity [43]. Subjects with this polymorphism are obese and more susceptible to chronic diseases, such as hypertension, bronchial asthma, and mood disorders [44,45]. Furthermore, one point mutation in the NR3C1 gene has been associated with primary generalized glucocorticoid hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Addison’s disease carrying the polymorphic BclI allele in a homozygous variant had a higher prevalence of central adiposity, impaired glucose tolerance, diabetes mellitus and dyslipidemia [ 149 ]. Studies have also shown greater susceptibility to cardiovascular disease in men with the BclI haplotype [ 150 , 151 ].…”
Section: Glucocorticoid Receptor Polymorphisms In Type 2 Diabetes Mellitusmentioning
confidence: 99%